Impact Strength of Hybrid Joints - Jan Godzimirski; Andrzej Komorek (Technologia i Automatyzacja Montażu)
Hybrid adhesive-mechanical joints compared to only adhesive or only mechanical joints are characterized by many advantages: greater stiffness, greater static strength, greater fatigue life, higher reliability, corrosion resistance. For these reasons, they are eagerly used in aviation structures. The aim of the research was to check the influence of hybridization on the impact toughness of connections. The static strength and the energy of dynamic destruction of lap joints loaded in shear by stretching or bending were compared: adhesive, riveted and hybrid joints. The tested hybrid joints were characterized by higher strength and dynamic destruction energy compared to adhesively bonded or riveted samples. The research also shows that the energy of dynamic failure increases if the failure of the joint is not complete and causes the connected elements to rotate around one rivet.